Pengaruh Tiktok Shop Terhadap Gaya Hidup dan Budaya Konsumtif di Kalangan Mahasiswa Junalisitk UIN Syarif Hidayatullah Jakarta - Iraka, Iwan; Siti Sarah Amelia; Erlina Ayu Lestari; Kholis Ridho (AT-TAWASUL, 2025)
The research entitled "The Influence of TikTok Shop on Lifestyle and Consumer Culture among UIN Jakarta Journalism Students" aims to find out how influential TikTok Shop is as an e-commerce platform for UIN Jakarta students. And does their use of TikTok Shop influence their lifestyle and change them into being consumptive in shopping? This research uses qualitative methods, namely by conducting interviews with 30 UIN Jakarta students. Based on the results of the analysis, researchers found that there is an influence of TikTok Shop on their lifestyle needs and consumer culture. And the TikTok Shop algorithm which is quite sophisticated in recommending products means that students tend to be exposed to relevant items according to their preferences. With very diverse impacts starting from lifestyle, shopping preferences and financial management. It can be concluded that TikTok Shop is not just a shopping platform, but part of the influence of digital culture which actively shapes consumption patterns in the younger generation, especially students.